Etiologies and Risk Factors of Placental Abruption and Neonatal Mortality: A Retrospective Study [6K]. (May 2017) - Araji, Sarah; Khoury, Aldo; Elkafrawi, Deena; Miller, Jacob
Abstract : INTRODUCTION: Placental abruption is defined as bleeding at the decidual-placental border leading to placental separation prior to delivery of the fetus. Placental abruption is a significant cause of maternal and perinatal mortality. In this retrospective study, we aim to evaluate the correlation between various causes and risk factors of placental abruption and neonatal mortality. METHODS: A retrospective chart review of placental abruption patients at SJRMC between 1986-1996 was conducted. Preeclampsia, eclampsia, HELLP, CHTN, preterm labor and placenta previa were recorded. Smoking, alcohol and cocaine use were assessed. Perinatal morbidity was based on length of NICU stay; neonatal mortality was defined as stillbirth or death. RESULTS: Our sample size was 271 pregnant women with placental abruption. Sixteen of 271 had HELLP (5.90%), 76 of 271 had preeclampsia (28.0%), and 22 of 271 had CHTN (8.11%). Forty of 271 used cocaine (14.7%), 104 of 271 smoked (38.4%) and 45 of 271 used alcohol (16.6%). Nine of 271 pregnant women with placental abruption had placental previa (3.32%). 37 of 271 infants were stillborn (13.6%) and 44 of 271 were dead on discharge (16.2%). HELLP syndrome was directly proportional to infant death (P=0.026; 95% CI, 0.26 to 4.03). Preeclampsia was proportional to neonatal mortality (P=0.000); CHTN was statistically significant for neonatal mortality (P=0.0010). Cocaine and alcohol correlated with increased neonatal mortality (P=0.0057; P=0.0220). CONCLUSION: CHTN, HELLP, preeclampsia, and placenta previa as causes of placental abruptions were found to be statistically significant predictors of neonatal mortality. Smoking, cocaine and alcohol use were directly proportional to neonatal mortality.